Pengenalan Dasar Pembuatan Website HTML Dengan Software Visual Studio Code - Arisky Rahmatulloh; Gunawan Atmaja; Halim Wijaya; Indrawan Indrawan; Irwan Ahussalim; Opik Hidayat Abdul Latif; Ramadhana Eka; Rizky Gimnastiar; Ridho Hafizh Maulana; Samsoni Samsoni; Ahmad Fadli (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Based on the life cycle of today’s society which cannot be separated from the use of technology and digitalization in all aspects of activity. The use of the website is no exception for various things, starting from business or just spreading the information you have. However, many people especially middle-level students don’t know how to make a website. Because of that, we took the software to the target obtained from this socialization are that students are able to make simple website display examples that can be developed according to their respective designations and goals.